2008
DOI: 10.1007/s10646-008-0214-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental behavior and ecotoxicity of engineered nanoparticles to algae, plants, and fungi

Abstract: Developments in nanotechnology are leading to a rapid proliferation of new materials that are likely to become a source of engineered nanoparticles (ENPs) to the environment, where their possible ecotoxicological impacts remain unknown. The surface properties of ENPs are of essential importance for their aggregation behavior, and thus for their mobility in aquatic and terrestrial systems and for their interactions with algae, plants and, fungi. Interactions of ENPs with natural organic matter have to be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
849
5
40

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,560 publications
(914 citation statements)
references
References 143 publications
20
849
5
40
Order By: Relevance
“…Spartina alterniflora had the lowest C f among tested biota and accounted for only 0.20% of the total recovered gold. This was surprising given reports of other vascular plants taking up nanomaterials 17,18 ; however, it is possible that the nanorods in this study were either too large for uptake or were unable to penetrate the sediments to reach the Spartina roots on the 12-day timescale.…”
Section: Nmcontrasting
confidence: 64%
“…Spartina alterniflora had the lowest C f among tested biota and accounted for only 0.20% of the total recovered gold. This was surprising given reports of other vascular plants taking up nanomaterials 17,18 ; however, it is possible that the nanorods in this study were either too large for uptake or were unable to penetrate the sediments to reach the Spartina roots on the 12-day timescale.…”
Section: Nmcontrasting
confidence: 64%
“…The sources of NPs to the environment are complex, consisting of both point and diffuse releases. During industrial production and transportation, accidental spills may occur [23]. Emissions to the atmosphere may result in deposition to soils and waters from various sources (e.g., waste incineration).…”
Section: Sources Of Metal-based Nps In Soilmentioning
confidence: 99%
“…In these studies, the particles are typically found to be agglomerated/aggregated, for example, TiO 2 [53,62,65,66], ZnO [43,53,[66][67][68], Ag [23,69], SiO 2 [70], and CeO 2 [53]. Manzo et al [71] analyzed an ZnO NP-contaminated soil by the Brunauer-Emmett-Teller method and found that the particles were not aggregated.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…As highlighted by the literature, the toxicity of n-TiO2 is influenced by: i) type of n-TiO2: crystalline structure, nominal size, content of impurities Navarro et al, 2008;Ji et al, 2011;Seitz et al, 2013;Seitz et al, 2014); ii) procedure followed to conduct the toxicity test, i.e. suspension preparation method with use of solvent, sonication, filtration, (Clement et al, 2013;Arouja et al, 2009; and iii) mode of exposure to organism i.e.…”
Section: The Effect Factor Calculationmentioning
confidence: 99%